2022
DOI: 10.3390/nano12203620
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Nanosensors Based on Green Synthesized CoFe2O4/Ca-Alginate Nanocomposite-Coated QCM for Rapid Detection of Pb(II) Ions

Abstract: Pb(II) is a significant contaminant that is known to have negative effects on both humans and animals. Recent industrial operations have exacerbated these consequences, and their release of several contaminants, including lead ions, has drawn attention to the potential effects on human health. Therefore, there is a lot of interest in the rapid, accurate, and selective detection of lead ions in various environmental samples. Sensors-based nanomaterials are a significant class among the many tools and methods de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A similar preparation method to the aqueous extract of Ocimum basilicum using the chitosan nanocapsule has been investigated [ 28 ]. The CNNC was characterized using several techniques [ 47 ], which confirmed the synthesis process of the nano form. The XRD pattern in this study confirmed the amorphous nature of CNNC with a good coating of neem extract by the chitosan nanocapsule.…”
Section: Discussionmentioning
confidence: 95%
“…A similar preparation method to the aqueous extract of Ocimum basilicum using the chitosan nanocapsule has been investigated [ 28 ]. The CNNC was characterized using several techniques [ 47 ], which confirmed the synthesis process of the nano form. The XRD pattern in this study confirmed the amorphous nature of CNNC with a good coating of neem extract by the chitosan nanocapsule.…”
Section: Discussionmentioning
confidence: 95%
“…Functional N-and S-co-doped carbon dots for detection of trace amounts of Fe 3+ with detection limit as low as 1.72 nM were reported by Cui et al, 140 Nitrogen-doped graphene quantum dots (N-GQD) for portable detection of Fe 3+ were introduced by Yao et al, 141 The N-GQD showed high production yield of 64% and high blue fluorescence providing a new strategy for controlling Fe3+ levels in environmental water. Functionalized CoFe 2 O 4 /Ca-alginate nanocomposite was designed by Al-Gethami et al, 142 as nanosensor for detection of Pb 2+ ions in aqueous solutions at different temperatures. High sensitivity, stability, and rapid detection are among the reported properties of the proposed sensor, while the lowest detection limit for Pb 2+ ions could reach 125 ng.…”
Section: Inorganic Pollutants -Heavy Metalsmentioning
confidence: 99%
“…To treat wastewater, numerous environmentally friendly and physicochemical techniques have been developed, such as filtration, adsorption, chemical degradation, biodegradation, photodegradation, and precipitation. [15][16][17][18] Among these methods, physical adsorption processes are considered reliable due to their efficiency and simplicity of operation and preparation. They are often preferred as they offer a cost-effective approach to water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is crucial to implement necessary measures to reduce water contamination caused by dye effluents. To treat wastewater, numerous environmentally friendly and physicochemical techniques have been developed, such as filtration, adsorption, chemical degradation, biodegradation, photodegradation, and precipitation 15–18 . Among these methods, physical adsorption processes are considered reliable due to their efficiency and simplicity of operation and preparation.…”
Section: Introductionmentioning
confidence: 99%